Peduli Lingkungan melalui Persediaan Tempat Sampah Pilah di Desa Setren, Kecamatan Rejoso, Kabupaten Nganjuk - Miftah Nur; Meimy Ratnakanyaka; Najwa Belvana; Nazhmi Fadhil; Andini Rahmawati; Hendra Maulana (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Economic growth and increasing population density in adulthood require awareness regarding environmental concern. Caring for the environment is an important thing that must be done to prevent natural damage and maintain ecosystem balance. Nganjuk Regency, with a population density of around 1,103,902 people in 2020, of course produces quite a lot of household waste. There is a need to increase awareness and change attitudes regarding waste sorting and processing to create a clean and healthy environment, which is the aim of holding waste bin procurement activities. Seeing that Setren Village SDGs number 12, namely Environmentally Conscious Village Consumption and Production, still has not met the target score that must be achieved, knowledge regarding waste sorting needs to be emphasized more. The method used was direct observation in the Setren Village environment, then a Focus Group Discussion was held regarding handling waste problems to create a healthy environment. The results of the community service carried out are the provision of waste sorting bins and socialization of waste sorting. Apart from that, there has been an increase in knowledge regarding types of waste for the people of Setren Village.